Development of Organ-on-Chip for the Study of Placental Pathologies: A Ten-Year Study of Literature Published - Ravindra Kalode; Pranoti Kalode (Health Technology Assessment in Action, 2023)
Abstract Context: The placenta performs a crucial function in nutrient exchange, but studying this tissue poses a number of challenges. Utilizing microfluidic and microfabrication technologies, a 3D placenta-on-a-chip model provides a biomimetic alternative for studying placental diseases and treatments. Objectives: Aim: To review and analyze the currently available placenta-on-chip data to study placental pathologies in patients. Methods: By systematically searching the PubMed, Scopus, and Science Direct databases, research papers that employed 3D printing techniques for the development of organoids and Organ-on-Chip (OoC) systems for in vitro experiments were gathered and scrutinized. Results: When exposed to glucose transfer, placenta-on-a-chip mimics the features of an in vivo human placenta. Microchips have the potential to become a platform for diagnostic purposes for placental diseases and a model for duplicating the important features of these diseases. Conclusions: The microfluidic placenta-on-a-chip platform holds promise as an affordable solution with versatile applications. However, research is essential to develop a comprehensive in vitro pregnancy model in the future to expand our understanding of feto-maternal communication.